PENGARUH KOMITMEN ORGANISASI DAN TIME BUDGET PRESSURE PADA KINERJA AUDITOR DENGAN BUDAYA THK SEBAGAI PEMODERASI - Ariantini, Ni Kadek Linda; Widhiyani, Ni Luh Sari (E-Jurnal Akuntansi, 2017)
The purpose in this research is to examine the influence of organizational commitment and time budget pressure on the performance of auditors to THK culture as moderating in KAP in Bali Province. The questionnaire used as the data collection methods that get 41 samples with non-probability sampling techniques. Multiple Linear Regression Analysis and Moderated Regression Analysis is an analytical technique used. The hypothesis was tested by looking at the value of coefficient determination test, test the feasibility of the model and t test. This study obtained results that organizational commitment has positive influence on the performance of auditors and time budget pressure negative effect on the performance of auditors. The study also obtain culture results THK able to strengthen the influence of organizational commitment on the performance of auditors, but the culture of THK not be able to weaken the influence of time budget pressure on the performance of auditors.
Keywords: Organizational Commitment, Time Budget Pressure, Culture THK and Performance Auditor